KREATIVITAS PESERTA DIDIK ANAK SEKOLAH DASAR (SD) MELALUI PEMBELAJARAN BAHASA INDONESIA DENGAN PENDEKATAN SCIENTIFIC - Anggun Citra Dini Dwi Puspitasari (Trapsila: Jurnal Pendidikan Dasar, 2020)
The 2013 curriculum is a further step in the development of the Competency-Based Curriculum which was initiated in 2004 and the 2006 KTSP which includes competency in attitudes, knowledge and skills in an integrated manner. The implementation of the 2013 curriculum on indonesian can be done through a scientific approach, which is to provide understanding to students in recognizing, understanding various materials using a scientific approach, that information can come from anywhere, at any time, does not depend on direct information from the teacher, which includes the stages of observing, asking, gathering information, processing information, communicating, and creating. Creativity is the ability to think, behave, and act in a new and rare way in solving a problem, resulting in an original and useful solution. Indicators of learning creativity are as follows: a) have curiosity, b) often ask constructive questions, c) provide many ideas and suggestions on a problem, d) are free to think in learning. Implementation of the 2013 curriculum, namely teachers as the spearhead of curriculum implementation that encourages students to be better able to observe, ask questions, reason, try and form networks of what they get or know after receiving learning material.